ANALISIS FAKTOR YANG MEMPENGARUHI KEPUASAN KERJA SDM - Neng Wardah Ramadaniatul Millah; Nisa Fariha Amalia Putri; Sri Damayanti; Riswandy Hapiddin Saleh; Abdul Kholik (Program Studi Manajemen Pendidikan Islam, 2023)
This study aims to describe job satisfaction on internal and external factors that affect teacher job satisfaction. Each type becomes a supporting and inhibiting factor that affects teacher performance. The research instrument is an interview, in qualitative descriptive learning. From the results that can be obtained in this study is that the job satisfaction of teachers at the al-bunyan Islamic boarding school has largely been fulfilled, for more details, the researcher describes the results of the study specifically as follows: Factors that influence job satisfaction of human resources at Al-bunyan Islamic boarding school, namely: (1) psychological factors, (2) social factors, (3) physical factors, (4) financial factors. Psychological factors consist of factors related to social interactions between (Education HR Job Satisfaction) fellow members of the organization, relationships with directors, direct superiors, employees with different job functions, volunteers. Supporting and inhibiting factors that affect HR job satisfaction are: Supporting factors consist of: the involvement of all stakeholders, the availability of sufficient personnel, infrastructure, facilities and financing, the support of all stakeholders, the community, and related active agencies, conducting regular and scheduled monitoring and evaluation. Thus the results of this study are expected to contribute to the world of science and technology. From the results of the study, it can be concluded that the satisfaction of learning activities at Pondok Pesantren Al-bunyan can be influenced by services at school, teacher welfare, and positive factors can improve student learning outcomes.